2018
DOI: 10.1111/are.13648
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dietary probiotic Bacilli (Bacillus subtilisandBacillus licheniformis) on growth performance, feed efficiency, body composition and immune parameters of whiteleg shrimp (Litopenaeus vannamei) postlarvae

Abstract: The present study investigates the effects of dietary commercial Bacilli probiotic (Bacillus subtilis and Bacillus licheniformis) on the growth performance, feed efficiency, body composition and immune parameters of Litopenaeus vannamei. The L. vannamei postlarvae were supplied and acclimated (in 500‐L tanks) to laboratory conditions for 14 days. The shrimps were fed with diets containing 1 × 104 and 1 × 108 CFU/g probiotic Bacilli for 60 days. At the end of the feeding trial, growth performance parameters, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(54 citation statements)
references
References 65 publications
(101 reference statements)
6
34
0
4
Order By: Relevance
“…Growth-promoting effects of BS have been reported in parrot fish (Oplegnathus fasciatus; Liu, Wu, Chu, & Wu, 2018) and red sea bream (Pagrus major; Zaineldin et al, 2018). The improved growth performance caused by BS administration was also reported in shrimp (Sadat Hoseini Madani, Adorian, Ghafari Farsani, & Hoseinifar, 2018) and sea cucumber (Apostichopus japonicas; Zhao et al, 2012). However, the administration of BS in large yellow croaker and mud crab (Scylla paramamosain) diets showed no remarkable effects on growth performance (Ai et al, 2011;Yeh, Chiu, Shiu, Huang, & Liu, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Growth-promoting effects of BS have been reported in parrot fish (Oplegnathus fasciatus; Liu, Wu, Chu, & Wu, 2018) and red sea bream (Pagrus major; Zaineldin et al, 2018). The improved growth performance caused by BS administration was also reported in shrimp (Sadat Hoseini Madani, Adorian, Ghafari Farsani, & Hoseinifar, 2018) and sea cucumber (Apostichopus japonicas; Zhao et al, 2012). However, the administration of BS in large yellow croaker and mud crab (Scylla paramamosain) diets showed no remarkable effects on growth performance (Ai et al, 2011;Yeh, Chiu, Shiu, Huang, & Liu, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, probiotics are used worldwide in eco-friendly and sustainable aquaculture practices, and their application are getting more and more attention due to their positive impact towards growth and/or health benefits of aquatic animals (Chauhan & Singh, 2018;Hai, 2015;Nayak, 2010). Bacillus strains possess growth-promoting potential, and evidence from previous studies have demonstrated that Bacillus bacteria served as probiotics and had a positive impact on the growth of aquatic animals, e.g., Nile tilapia (Oreochromis niloticus; Liu, Wang, et al, 2017), red sea bream (Pagrus major; Zaineldin et al, 2018), sea cucumber (Apostichopus japonicas; Yang, Tian, Dong, Peng, & Wang, 2015) and whiteleg shrimp (Litopenaeus vannamei; Sadat, Adorian, Ghafari, & Hoseinifar, 2018). Similarly, our results indicated that dietary supplementation with 1 × 10 9 CFU/kg B. cereus exhibited significantly increased growth of Pengze crucian carp, and similar results was observed in other fish like ambaqui (Dias et al, 2018), rainbow trout (Oncorhynchus mykiss; Gisbert, Castillo, Skalli, Andree, & Badiola, 2013), and Clarias gariepinus (Reda et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our data, other works have reported an increase in lysozyme activity by supplementing Bacillus spp. to the diets and adding to the water (Kewcharoen & Srisapoome, 2019;Sadat Hoseini Madani, Adorian, Ghafari Farsani, & Hoseinifar, 2018).…”
Section: Immunohematological and Haemolymph Biochemistry Parametersmentioning
confidence: 99%